Speaker Abstracts 2001 2001
DOI: 10.1136/annrheumdis-2001.347
|View full text |Cite
|
Sign up to set email alerts
|

OP0055 Sulfasalazine improves the number of flares of acute anterior uveitis over a one year period

Abstract: 0-10). Utilities were measured with the EuroQoL (EQ-5D utility ) (range 0-1). A time-integrated summary score defined the clinical effects (BASFI-AUC) and utilities (EQ-5D utility -AUC) over time. Both direct (health care and non-health care) and indirect costs were included. Resource utilisation and absence from paid work were registered weekly by the patients in a diary. All costs were calculated from a societal perspective. Results 111 patients completed the diary (group 1 n = 38; group 2 n = 36; control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Our study is in line with previously published data on the effect of SSZ in AAU regarding reduction of severity and number of flares (20,21,27). We can now demonstrate a similar efficacy of MTX in reducing flare rate and, moreover, observe a beneficial effect in patients presenting with CME, a severe vision-threatening complication of AAU.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study is in line with previously published data on the effect of SSZ in AAU regarding reduction of severity and number of flares (20,21,27). We can now demonstrate a similar efficacy of MTX in reducing flare rate and, moreover, observe a beneficial effect in patients presenting with CME, a severe vision-threatening complication of AAU.…”
Section: Discussionsupporting
confidence: 92%
“…Sulfasalazine (Azulfidine, SSZ) is a classical DMARD that has been extensively studied and is often used for first-line medical treatment of rheumatoid arthritis (RA) and inflammatory bowel disease since its use was approved in the USA in 1950. SSZ has previously been suggested as potential treatment for AAU [21] and a reduction in flare rate and severity of AAU by this treatment has been described [20,21]. Sieper et al suggested a similar efficacy for SSZ and the TNF inhibitor etanercept in preventing uveitis relapses [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of maintenance therapy depends on the underlying rheumatic features. In patients with frequent recurrences (at least 2-3/year) and mild rheumatic manifestations, SSZ, which had been evaluated in a small study [93] and in a randomized trial including 22 patients [94], is an option [91]. An open clinical trial on 9 patients also suggested the efficacy of MTX at an initial dose of 7.5 to 20 mg/week to reduce the rate of recurrence of AU in patients who had more than 3 recurrences of AU in the past year [95].…”
Section: Treatmentmentioning
confidence: 99%
“…En el caso de ataques recurrentes de uveítis, los antiinflamatorios no esteroideos (AINE) pueden aliviar los síntomas por un período corto 30 . Las DME convencionales como sulfasalazina (SSZ) y metotrexato (MTX) tienen una evidencia limitada en el tratamiento de esta manifestación [31][32][33][34][35] . En este estudio, si bien se observó significativamente mayor frecuencia de tratamiento con DME en los pacientes con UAA, no fue posible discriminar si la DME fue indicada como parte del tratamiento para el compromiso ocular o para alguna otra manifestación.…”
Section: úLtimo Episodiounclassified